Implementation of Artificial Intelligence–Integrated Project-Based Learning to Enhance Digital Entrepreneurship Literacy and Student Engagement in Economics Education - Hariyono; Umi Hidayati; Suharto (Universitas Sulawesi Barat, 2026)
The rapid advancement of digital technology and artificial intelligence (AI) has significantly influenced higher education practices, demanding innovative pedagogical models that foster students’ digital competence, creativity, and engagement. This study aimed to analyze the effectiveness of an artificial intelligence (AI)-integrated project-based learning (PjBL) model in improving digital entrepreneurship literacy (DEL) and learning engagement (LE) among students in economics education. This study employed a two-cycle classroom action research design involving 28 third-semester students enrolled in the Microeconomics course at Universitas Nusantara PGRI Kediri. Data were collected using six instruments: the Digital Entrepreneurship Literacy Scale, the Learning Engagement Scale, the project rubric, the observation sheet, the digital activity log, and reflective interviews. Quantitative analyses included paired-samples t-tests, N-gain, and Pearson correlations, while qualitative data were analyzed thematically. The results showed a significant improvement in both DEL and LE following implementation of the AI-integrated PjBL model. The mean DEL score increased from 76.04 to 102.96 (n-gain = 0.623; p < 0.001), and the mean LE score increased from 60.75 to 79.75 (n-gain = 0.661; p < 0.001). Observations and digital activity logs revealed higher behavioral and cognitive engagement during the learning process. Qualitative findings indicated that students utilized AI tools such as ChatGPT, Google Sheets AI, Gemini, and Canva AI for market research, price elasticity simulations, and digital content design in creative and ethical ways. The study concludes that integrating AI into the PjBL framework effectively enhances students’ digital entrepreneurship literacy, fosters reflective engagement, and supports the development of adaptive, ethical, and innovative learners in economic education.